2010
DOI: 10.1002/mats.200900089
|View full text |Cite
|
Sign up to set email alerts
|

Radical Desorption Kinetics in Emulsion Polymerization, 2 – Brownian Dynamics Simulation of Radical Desorption in Non‐Homogeneous Particles

Abstract: One of the most important events in free‐radical emulsion polymerization is desorption of radicals from the polymer particles to the aqueous phase. Desorption takes place by diffusion of radicals inside the particle toward the surface and transfer to the aqueous phase. The rate of desorption can be determined theoretically for homogeneous spherical particles. For more complex cases, analytical solutions become difficult or impossible to obtain and a numerical approach is better suited for estimating desorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Actually, the very core of the debate is the desorption rate of primary radical. Therefore, much effort has been paid to model the desorption process of radical . Nomura et al modeled the primary radical desorption rate according to the Einstein‐diffusion equation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, the very core of the debate is the desorption rate of primary radical. Therefore, much effort has been paid to model the desorption process of radical . Nomura et al modeled the primary radical desorption rate according to the Einstein‐diffusion equation .…”
Section: Introductionmentioning
confidence: 99%
“…Fellows et al explored the radical desorption rate by the mechanism of nonequilibrium diffusion. Asua investigated the radical desorption by Fick's law and Hernandez et al studied the radical desorption via the Brownian dynamics simulation . However, the desorption process is so microcosmic that less direct experiment evidence has been proposed to support the theoretical modeling.…”
Section: Introductionmentioning
confidence: 99%
“…While the desorption kinetic rate coefficient can be inferred from indirect measurements combined with kinetics involving some assumptions (refer to Thickett and Gilbert for an overview), the experimental validation of theoretical radical desorption models is challenging, particularly for complex systems where it is difficult to estimate key kinetic parameters. Hernandez and Tauer convincingly argue that Brownian dynamics simulations can be used to estimate desorption rate coefficients in increasingly‐complex systems and to validate existing theoretical desorption models.…”
Section: Fundamental Mechanisms Of Emulsion Polymerizationmentioning
confidence: 97%
“…However, it has been reported that the partition coefficient of PR should be used in the modeling of miniemulsion polymerization initiated by oil‐soluble initiator, because PR is more directly related to the polymerization than the initiator . Recently, Hernandez and Tauer have reviewed a range of models to estimate the radical desorption rate in emulsion polymerization . Among these models, the expression “ Desorption rate =Driving force Resistance ” was always used, but the assumptions of resistance terms were different.…”
Section: Introductionmentioning
confidence: 99%